International trade and finance frontiers for research - Kenen, Peter B. 1932-2012 (Cambridge University Press, 1975)
The nine papers in this volume were written for a conference on research in international trade and finance held at Princeton University in March 1973. Each author was asked to survey research on one major topic, with a view to answering three questions: What have we learned from recent empirical research? What are the major gaps in present knowledge? How should we go about filling those gaps? When answering the second question, authors were urged to look at the practical requirements of those who must make policy concerning the international economy, and at the opportunities and insights offered by recent developments in pure theory. When answering the third, they were urged to look at developments in econometric technique, newly available data, and work in progress in related fields